2021
DOI: 10.2196/29110
|View full text |Cite
|
Sign up to set email alerts
|

Low Carb Program Health App Within a Hospital-Based Obesity Setting: Observational Service Evaluation

Abstract: Background Obesity underlies much chronic disease. Digitalization of obesity management provides an opportunity to innovate our traditional model of health care delivery within this setting, and to transform its scalability potentially to the population level. Objective The objective was to assess the feasibility and effectiveness of the Low Carb Program app for weight loss, applied within our hospital-based (tier 3) obesity service. Due to the disrupti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…Indeed, at least in the short term (less than 6 months), such interventions result in greater weight loss than more traditional face-to-face interventions [ 6 ], with apparent equivalence in the overall effectiveness between these 2 approaches in the long term (12 months) [ 3 ]. Similar findings were observed in a feasibility study of the Low Carb Program app in our obesity service at UHCW, whereby digital tool interventions for diet combined with medical appointments resulted in a similar weight loss to that from a traditionally delivered obesity service [ 7 ]. Interestingly, there are no studies that explore the feasibility of offering digital tools to patients on a waiting list for a specialist weight management service, defined as a service comprising specialist dietitians, physicians, and psychologists.…”
Section: Introductionsupporting
confidence: 78%
“…Indeed, at least in the short term (less than 6 months), such interventions result in greater weight loss than more traditional face-to-face interventions [ 6 ], with apparent equivalence in the overall effectiveness between these 2 approaches in the long term (12 months) [ 3 ]. Similar findings were observed in a feasibility study of the Low Carb Program app in our obesity service at UHCW, whereby digital tool interventions for diet combined with medical appointments resulted in a similar weight loss to that from a traditionally delivered obesity service [ 7 ]. Interestingly, there are no studies that explore the feasibility of offering digital tools to patients on a waiting list for a specialist weight management service, defined as a service comprising specialist dietitians, physicians, and psychologists.…”
Section: Introductionsupporting
confidence: 78%
“…In fact, although one might think that a lockdown must necessarily reduce physical activity levels while increasing calorie intake, in fact, a relevant part of the population was able to take advantage of the lockdown to pay more attention to proper nutrition at home as opposed to for example, consuming frugal and unbalanced meals during work breaks outside the home in non-pandemic times. Conversely, others suffered greatly from social distancing and home isolation by compensating with food for their discomfort, indulging in sedentary living, and sometimes interrupting the daily physical activity they had previously partaken in [ 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have shown that DWMIs can be as effective as in-person interventions for weight loss and related outcomes for people with obesity [ 19 - 21 ], and the COVID-19 pandemic provided further evidence that existing intensive, in-person programs could be effectively transformed to deliver care remotely and effectively using technology [ 22 - 24 ]. Furthermore, 2 studies have shown that remote delivery of a weight management program in the UK can be as effective as usual face-to-face support in a tier 3 weight management service [ 18 , 25 ]. For example, a dietetic weight loss app program was found to be as effective and feasible when delivered remotely from a hospital-based SWMS to their usual face-to-face care [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 2 studies have shown that remote delivery of a weight management program in the UK can be as effective as usual face-to-face support in a tier 3 weight management service [ 18 , 25 ]. For example, a dietetic weight loss app program was found to be as effective and feasible when delivered remotely from a hospital-based SWMS to their usual face-to-face care [ 25 ]. However, real-world evidence of the potential for digital intervention to support SWMS in the UK National Health Service (NHS) remains limited [ 26 ].…”
Section: Introductionmentioning
confidence: 99%